Functional role of Runx3 in the regulation of aggrecan expression during cartilage development. Issue 11 (25th July 2013) - Wigner, Nathan A.; Soung, Do Y.; Einhorn, Thomas A.; Drissi, Hicham; Gerstenfeld, Louis C.
Abstract Runx2 and Runx3 are known to be expressed in the growth plate during endochondral bone formation. Here we addressed the functional role of Runx3 as distinct from Runx2 by using two models of postnatal bone repair: fracture healing that proceeds by an endochondral process and marrow ablation that proceeds by only an intramembranous process. Both Runx2 and Runx3 mRNAs were differentially up regulated during fracture healing. In contrast, only Runx2 showed increased expression after marrow ablation. During fracture healing, Runx3 was expressed earlier than Runx2, was concurrent with the period of chondrogenesis, and coincident with maximal aggrecan expression a protein associated with proliferating and permanent cartilage. Immunohistological analysis showed Runx3 protein was also expressed by chondrocytes in vivo. In contrast, Runx2 was expressed later during chondrocyte hypertrophy, and primary bone formation. The functional activities of Runx3 during chondrocyte differentiation were assessed by examining its regulatory actions on aggrecan gene expression. Aggrecan mRNA levels and aggrecan promoter activity were enhanced in response to the over‐expression of either Runx2 and Runx3 in ATDC5 chondrogenic cell line, while sh‐RNA knocked down of each Runx protein showed that only Runx3 knock down specifically suppressed aggrecan mRNA expression and promoter activity. ChIP assay demonstrated that Runx3 interactions were selective to sites within the aggrecan promoter and were only observed during early periods of chondrogenesis before hypertrophy. Our studies suggest that Runx3 positively regulates aggrecan expression and suggest that its function is more limited to cartilage development than to bone. In aggregate these data further suggest that the various members of the Runx transcription factors are involved in the coordination of chondrocyte development, maturation, and hypertrophy during endochondral bone formation. J. Cell. Physiol. 228: 2232–2242, 2013. © 2013 Wiley Periodicals, Inc.